2021
DOI: 10.1186/s13046-021-01943-5
|View full text |Cite
|
Sign up to set email alerts
|

KLF5-induced BBOX1-AS1 contributes to cell malignant phenotypes in non-small cell lung cancer via sponging miR-27a-5p to up-regulate MELK and activate FAK signaling pathway

Abstract: Background Non-small cell lung cancer (NSCLC) is a major histological subtype of lung cancer with high mortality and morbidity. A substantial amount of evidence demonstrates long non-coding RNAs (lncRNA) as critical regulators in tumorigeneis and malignant progression of human cancers. The oncogenic role of BBOX1 anti-sense RNA 1 (BBOX1-AS1) has been reported in several tumors. As yet, the potential functions and mechanisms of BBOX1-AS1 in NSCLC are obscure. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…LncRNA gamma-butyrobetaine hydroxylase 1 (BBOX1)-antisense RNA 1 (AS1) exists as an oncogene in most tumor cells. Abnormally high expression levels of BBOX1-AS1 are observed in most cancers, such as lung [ 7 ], cervical [ 8 ], and esophageal cancers [ 9 ], and BBOX1-AS1 is strongly linked to the overall survival of patients with these cancers, which suggests that targeting BBOX1-AS1 may be used as a therapeutic approach for cancer treatment. However, the regulatory effects of BBOX1-AS1 on OSCC development have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA gamma-butyrobetaine hydroxylase 1 (BBOX1)-antisense RNA 1 (AS1) exists as an oncogene in most tumor cells. Abnormally high expression levels of BBOX1-AS1 are observed in most cancers, such as lung [ 7 ], cervical [ 8 ], and esophageal cancers [ 9 ], and BBOX1-AS1 is strongly linked to the overall survival of patients with these cancers, which suggests that targeting BBOX1-AS1 may be used as a therapeutic approach for cancer treatment. However, the regulatory effects of BBOX1-AS1 on OSCC development have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Many current research work have revealed that the interaction between lncRNA and specific miRNA can regulate cancer progression [7,10,13]. Furthermore, since miRNA is absorbed by lncRNA and targets mRNA, it is thought to be a significant regulator in biologic processes [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific role of BBOX1-AS1 in pituitary adenoma is still rarely reported. Many current research works have revealed that the interaction between specific miRNA and lncRNA can regulate cancer progression [7,10,13]. Previous studies showed that BBOX1-AS1 sponging miR-361-3p results in abrogation of the antitumorigenic potential of miR-361-3p in different cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the LRSI group, KLF5 was the most significant gene for CNV in the HRSI group. KLF5 plays an important role in the DNA damage response by regulating DNA damage checkpoint proteins and is associated with cisplatin DDP resistance [ 33 35 ]. The relationship between KLF5 and radiotherapy sensitivity needs to be discovered.…”
Section: Discussionmentioning
confidence: 99%